1993
DOI: 10.1063/1.354955
|View full text |Cite
|
Sign up to set email alerts
|

Conducting thin films of pentacene doped with alkaline metals

Abstract: Electrical properties of highly ordered and amorphous thin films of pentacene doped with iodine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 13 publications
0
40
2
1
Order By: Relevance
“…1, DOS approximately resembles the undoped bands in this case. The possibility of spin polarization is marginal for this structural model (see Table I structure is energetically unlikely, perhaps the detailed way in which samples are grown matters and could eventually explain metallic behavior [10,11,14]. In any case, as said previously, interlayer doping is limited to one electron (K atom) per pentacene molecule.…”
Section: A Kpentacene Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…1, DOS approximately resembles the undoped bands in this case. The possibility of spin polarization is marginal for this structural model (see Table I structure is energetically unlikely, perhaps the detailed way in which samples are grown matters and could eventually explain metallic behavior [10,11,14]. In any case, as said previously, interlayer doping is limited to one electron (K atom) per pentacene molecule.…”
Section: A Kpentacene Compoundmentioning
confidence: 99%
“…Results given in Refs. [10,11,14] could be understood in this context. On the other hand, additional experimental results point to a prompt metal-insulator transition at the first stages of doping [15][16][17].…”
Section: A Kpentacene Compoundmentioning
confidence: 99%
“…These results were slightly modified [10], but yielded both a characteristic d(0 0 1) value of 14.4 A . In 1991, Minakata et al reported on the growth and crystal structure of thin films [11,12]. They reported for thin films d(0 0 1) spacings of 15.0 and 15.4 A .…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, different d(0 0 l) values are reported for pentacene thin films [4,11,12,19]. To investigate this, we have grown thin films of pentacene, using different growth conditions.…”
Section: Growth Of the Different Polymorphs On Thin Filmsmentioning
confidence: 99%
“…Bulk KxPentacene (x = 1, 2 and 3.6) has previously been reported without structural characterisation, [17][18][19] and metallic conductivity has been reported in potassium-doped pentacene thin films. [20][21][22][23][24] As pentacene is more readily available than picene, we chose initially to address the synthesis of potassium-intercalated pentacene samples suitable for structural analysis, before applying these protocols to the picene system. …”
mentioning
confidence: 99%